Web Data Analytics and Tools - A Review - S. Vinothini,; K.Vishwa,; M. Ninushiya,; V. Arthi,; M. Arunachalam, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The objective of web analytics is to function as a business metric for promoting specific products to the purchasers who are presumably to shop for them and to work out which products a selected customer is presumably to get. This helps improve the ratio of revenue to marketing costs.In addition to those features, web analytics may track the clickthrough and drill down behavior of consumers within an internet site, determine the sites from which customers most frequently arrive, and communicate with browsers to track and analyze online behavior. The results of web analytics are provided within the sort of tables, charts and graphs.
Keywords: Web Analytics; Web Data Analytics; Clickstream; CI; VOC; Data insights; Strategy Planning